2018
DOI: 10.1007/s11695-018-3280-2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation in Morbid Obese Patients Undergoing One Anastomosis Gastric Bypass-Mini Gastric Bypass (OAGB-MGB) Surgery: a Randomized, Double-Blind, Placebo-Controlled, Clinical Trial

Abstract: This study has been registered at Clinicaltrial.gov with registration number NCT02708589.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…We identified 1934 records, from which we selected 986 individual abstracts and 161 potentially relevant articles for full review (figure 1). We identified 105 articles19 25–128 reporting data from 99 different research studies including 111 different randomised comparisons of probiotics versus control (further called randomised clinical trials [RCTs], see online supplementary table 1-2) with the following outcomes: BW (number of RCTs: k=58, n=3422 individuals, median=77.4 kg), BMI (k=68, n=4015, 28.2 kg/m²), WC (k=26, n=1583, 98.8 cm); BFM (k=27, n=1562, 27.8 kg), SAT and VAT (k=5, n=543, 192.4 cm² and 114.7 cm², respectively), FG (k=83, n=5188, 6.1 mmol), HbA 1c (k=28, n=1796, 6.3%), INS (k=63, n=3854, 11.0 mU/L), HOMA-IR (k=52, n=3513, 3.2), CRP (k=41, n=2376, 3.6 mg/L), TG (k=74, n=4461, 145.4 mg/dL), ALAT (k=26, n=1466, 38.6 IU/L), ASAT (k=23, n=1340, 36.1 IU/L) and GGT (k=14, n=816, 41.5 IU/L). The median duration of the follow-up was 8 weeks (range: 2–28 weeks), probiotics dose ranged from 10 7 to 10 12 CFU daily, and 43 trials were conducted in one country (Iran).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 1934 records, from which we selected 986 individual abstracts and 161 potentially relevant articles for full review (figure 1). We identified 105 articles19 25–128 reporting data from 99 different research studies including 111 different randomised comparisons of probiotics versus control (further called randomised clinical trials [RCTs], see online supplementary table 1-2) with the following outcomes: BW (number of RCTs: k=58, n=3422 individuals, median=77.4 kg), BMI (k=68, n=4015, 28.2 kg/m²), WC (k=26, n=1583, 98.8 cm); BFM (k=27, n=1562, 27.8 kg), SAT and VAT (k=5, n=543, 192.4 cm² and 114.7 cm², respectively), FG (k=83, n=5188, 6.1 mmol), HbA 1c (k=28, n=1796, 6.3%), INS (k=63, n=3854, 11.0 mU/L), HOMA-IR (k=52, n=3513, 3.2), CRP (k=41, n=2376, 3.6 mg/L), TG (k=74, n=4461, 145.4 mg/dL), ALAT (k=26, n=1466, 38.6 IU/L), ASAT (k=23, n=1340, 36.1 IU/L) and GGT (k=14, n=816, 41.5 IU/L). The median duration of the follow-up was 8 weeks (range: 2–28 weeks), probiotics dose ranged from 10 7 to 10 12 CFU daily, and 43 trials were conducted in one country (Iran).…”
Section: Resultsmentioning
confidence: 99%
“…Different probiotic species and strains may have multiple modes of actions affecting sugar digestion and absorption,136 fat absorption,106 gut barrier function,112 115 137 low-grade inflammation, 39 71 81 99 110 111 116 138 bile acid metabolism,97 139 incretin secretion120 and gut microbiota ecosystems19 44 87 115 119 and, in particular, short chain fatty acid production 121. It is reasonable to anticipate that these multiple effects may combine to induce significant effects, particularly in the case of multispecies mixes.…”
Section: Discussionmentioning
confidence: 99%
“…Familact (Zist Takhmir Co., Tehran, Iran) is a probiotic mixture supplement that has shown efficacy in several diseases . Therefore, we conducted this randomized crossover clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Familact (Zist Takhmir Co., Tehran, Iran) is a probiotic mixture supplement that has shown efficacy in several diseases. [13][14][15][16][17][18] Therefore, we conducted this randomized crossover clinical trial. The aim of this study was to assess the impact of add-on probiotic supplement on PAR symptoms and on the QoL of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients administered microecological preparations following bariatric surgery show benefits in their quality of life (QoL), excess weight loss (EWL), vitamin accessibility, and inflammatory marker expression. Karbaschian et al [19] showed that probiotics stimulate weight loss in patients undergoing gastric bypass. However, another study [20] showed that administering probiotics does not improve anthropometric measurements in patients following laparoscopic SG.…”
Section: Introductionmentioning
confidence: 99%